Комплексное использование геолого-геофизических методов для выделения зон скоплений метана - Каргаполов, А.А.; Макеев, С.Ю.; Свистун, В.К.; Гуня, Д.П. (Геотехническая механика, 2012)
Стаття присвячена аналізу та обґрунтуванню можливості комплексного викор истання
методів геофізичних досліджень свердловин, гравірозвідці і геологічних методів для
виявлення та уточнення зон скупчення метану і місць локального прояву колекторів,
сприятливих для буріння дегазаційних свердловин. The article is sanctified to the analysis and ground of possibility by the complex use of
geophysical methods researches of mining holes, gravitational exploration and geological methods for a discovery and clarification of methane zones accumulation and places of collectors local display, which friendly to the boring drilling of decontamination mining holes.